2020
DOI: 10.3390/nano10122554
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Gas Sensing Material for Environmentally Toxic Gases Based on Janus NbSeTe Monolayer

Abstract: Recently, a new family of the Janus NbSeTe monolayer has exciting development prospects for two-dimensional (2D) asymmetric layered materials that demonstrate outstanding properties for high-performance nanoelectronics and optoelectronics applications. Motivated by the fascinating properties of the Janus monolayer, we have studied the gas sensing properties of the Janus NbSeTe monolayer for CO, CO2, NO, NO2, H2S, and SO2 gas molecules using first-principles calculations that will have eminent application in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 76 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…Many reported sensing studies have suggested an adsorption energy of more than 0.30 eV shows better gas adsorption. 38,56 Interestingly, our calculated adsorption energies (E ad ) of all the gas molecules except H 2 as shown in Table 1 satisfy this criterion. Table 1 and the above Fig.…”
Section: Adsorption Of Gas Molecules On the Mosse Monolayersupporting
confidence: 53%
See 1 more Smart Citation
“…Many reported sensing studies have suggested an adsorption energy of more than 0.30 eV shows better gas adsorption. 38,56 Interestingly, our calculated adsorption energies (E ad ) of all the gas molecules except H 2 as shown in Table 1 satisfy this criterion. Table 1 and the above Fig.…”
Section: Adsorption Of Gas Molecules On the Mosse Monolayersupporting
confidence: 53%
“…This eminent characteristics and its distinct transport properties were especially notable in a discrepancy in the I – V profile showing signatures of the Janus NbSeTe as a highly sensitive gas sensor (mainly for NO 2 gas) with a reformable scope. 38 Moreover, applying an electric field, strain, defect, etc. are also effectual approaches for the modulation of the sensing properties.…”
Section: Introductionmentioning
confidence: 99%
“…73 Similarly, the computed recovery time of CO 2 molecule is also lower than that of other nanomaterials such as 1T-HfTe 2 (33.7 ns), 74 SiBi (0.73 ps) 75 and NbSeTe (23.1 and 13.3 ps). 76 It should be noted that the charge transfer between Si 2 BN-ML and gas molecules is fundamentally associated with the electronegativity difference, chemical bonding properties as well as adsorption energy. As a general practice, the reasonable adsorption energy r1 eV is treated as the most suitable one for sensing applications with feeble chemisorption or steady physisorption.…”
Section: Mechanical and Electronic Propertiesmentioning
confidence: 99%
“…28 It is not unique, Dou et al found that the sensitivity of WTe 2 monolayer for CO, NO, and O 2 molecules is signicantly improved by constructing the Janus structure. 29 Inspired by the above research about Janus structure, [30][31][32] we envisaged to further enhance the adsorption performance of the MoSi 2 N 4 monolayer for NO and NO 2 molecules in this way. Excitingly, Yu et al proposed a 2D Janus structure of MoSiGeN 4 monolayer by rst-principles calculations, which indeed exhibited more excellent stability and semiconducting properties.…”
Section: Introductionmentioning
confidence: 99%